Empowering the Elderly to Create Gardens for Aromatherapy; Enhancing Healthy Life Expectancy - Wulandari, Ning Arti; Romadhon, Wimar Anugrah; Mildawati, Ratna (Journal of Community Service for Health, 2024)
Life expectancy is one of the indicators of the success of health development, especially in the elderly population. One way to improve Healthy Life Expectancy is through Active Aging, which aims to transform previously inactive seniors into active individuals, with the goal of extending life expectancy in a healthy and quality manner. The partner in this community's dedication was Blitar PSTW in Tulungagung who had an old age problem, lack of physical activity, poor quality of sleep and lack of use of empty land. The aim of the beginner community service program was to empower potential elderly individuals to produce aromatic materials in the form of essential oils and scented candles, starting from planting the plants that provide the raw materials, all the way to the production of aromatic materials to enhance their physical activity. The results of the data analysis used the Wilcoxon signed-rank test showed P=0.000, thus it can be concluded that the used of aromatherapy at night and increased physical activity through gardening and the activities of making aromatherapy materials conducted by the elderly can improved sleep quality. This service has produced an innovative technology product in the form of Standard Operating Procedures (SOP) for the production of essential oils and aromatherapy candles, aromatherapy candles, essential oils, and therapy gardens. The outcomes achieved in healthy living skills include utilizing free time by engaging in activities for the elderly (16%) and improving the quality of sleep for the elderly (86%).